Manpower planning using decision analysis: case of crown company (2008)
This study addresses the analytic approach to decision making and its application to manpower planning in the crown section of a bottling company in Nigeria. The company produces crowns for several bottling companies and was faced with the challenge of meeting customer's demand, which varied from month to month. A work sampling technique was used to investigate the discrepancy between the level of the work force and their output. The result of the work sampling study showed that all of the departments were overstaffed with idle time and that overtime, rather than additional shifts, would reduce manpower cost. The results have been applied to the management policies that can be employed to meet increasing short term demand.